Ten Common Flowering Trees of the Tampa Bay Area - Gitta Hasing; Andrew K. Koeser; Gary W. Knox; Melissa H. Friedman (EDIS)
Blooming trees serve as key focal points in the urban landscape. Florida’s flowering trees can be quite spectacular and leave you wondering, Wow, what tree is that?